Phytochemical Analysis of Flavonoids and Tannins from Ethanol Extract of Keji Beling (Strobilanthes crispus) Using UV-Vis Spectrophotometry Method - Ayu Safitri; Panji Wahlanto (LPPM STIKes Muhammadiyah Ciamis, 2023)
Keji Beling (Strobilanthes crispus BI.) is a plant that has been used by the community as a traditional medicine for kidney stones, diabetes mellitus, ulcers and as a laxative. Keji beling contains many beneficial substances such as flafonoids and tannins. This research aims to determine the content of flavonoid and tannin phytochemical compounds and to determine length Maximum waves in flavonoid and tannin compounds in keji beling leaf extract (Strobilanthes crispus BI.). Keji beling leaves were extracted using the maceration method with 70% ethanol solvent. Secondary metabolite content was identified qualitatively using a phytochemical screening test. Flavonoids were tested with concentrated MgSO4 and HCl reagents and tannins were tested with FeCl3 reagent. Qualitative analysis using the UV-Vis Spectrophotometry method. Results Research shows that the phytochemical screening test on keji beling leaf extract (Strobilanthes crispus BI.) is positive for containing flavonoids and tannins, indicated by a color change in the phytochemical screening test. Qualitative analysis results appear at a maximum wavelength of 465 nm for flavonoids, and for tannin compounds at a maximum wavelength of 765 nm.